Penerapan Model Pembelajaran Group Investigasi Dalam Meningkatkan Kemampuan Representasi Matematis - Hasibuan, Shubuhan Syukri; Hasibuan, Elis Rahmadani; Hasibuan, Sundut Azhari (Manna wa Salwa Foundation (Yayasan Manna wa Salwa), 2024)
The purpose of this research is to improve the ability of mathematical representation of Grade X OTKP 2023/2024 Academic Year during mathematics with implementation of investigation in increase ability representation mathematical . The type of research is classroom researh of two cycles based on teaching syllabus of the mathematics teacher in class x otkp . Each cycle is carried ot based on the competency standards to be achieved in learning. The cycle in this class action research through four stages, namely: planning of action; implementation of action; observation and evaluation; reflection. Based on the result of research conducted on the Grade x otkp 2023/2024 Academic Year on the competency standards: solving system of linear equation of one variable learning model in the group investigation improve the ability of mathematical representation, which are : respones and learning outcomes shown in cycle II are primly good and the students mathematical representation test capability in each cycle has improve signivicantly, until 80% on the last cycle. Moreover, the results showed that there are only 3 students from of 20 students who obtain score 70 which is the minimum completeness criteria set by the school . Therefore, learning by applying learning model group investigation can improve the ability of mathematical representation.